Feline infectious peritonitis: A comprehensive evaluation of clinical manifestations, laboratory diagnosis, and therapeutic approaches - Moyadee, Wassamon; Sunpongsri, Supita; Choowongkomon, Kiattawee; Roytrakul, Sittiruk; Rattanasrisomporn, Amonpun; Tansakul, Natthasit; Rattanasrisomporn, Jatuporn (Journal of Advanced Veterinary and Animal Research, 2024)
Objective: This study aimed to investigate the clinical and laboratory characteristics of naturally occurring feline infectious peritonitis (FIP) and estimate the median survival time of FIP cats treated with prednisolone to guide further therapeutic planning. Materials and Methods: In this retrospective study, data from a total of 116 cats with effusion were fully recorded. Forty-five FIP-diagnosed cats were enrolled for analysis. Results: The study findings indicate that FIP was a disease affecting cats aged 1–2 years and was highly prevalent among male cats. Clinical manifestations of FIP affected the digestive (60%), hematological (53.3%), respiratory (33.3%), neurological (6.7%), and ocular (4.4%) systems. Blood profiles revealed mild anemia, lymphopenia, thrombocytopenia, hypoalbuminemia, hyperglobulinemia, and an albumin to globulin ratio of 0.4. Fluid analysis and cytology of FIP cats demonstrated a transparent yellow fluid with a protein content of 6 gm/dl and a total nucleated cell count of approximately 5,000–10,000 cells. During the observation period, FIP cats treated with prednisolone exhibited a median survival time of 31 days. Conclusion: Confirming FIP cases can be challenging; therefore, a tentative diagnosis of FIP must be made with care. This study provided practical diagnostic tools to diagnose FIP based on clinical signs and multiple abnormalities, which allowed for more efficient and rapid detection. Adv. Vet. Anim. Res., 11(1): 19-26, March 2024 http://doi.org/10.5455/javar.2024.k742